روہیل کھنڈ کے افغان شاعرنواب محمد یار خاں امیرکے کلام کا تحقیقی و تنقیدی جائزہ: Critical and Research Review of the Afghan Poet Nawab Muhammad Yar Khan Ameer of Rohail Khand (Al-Qamar, 2023)
This research paper critically evaluates the work of Nawab M.Yar Khan Ameer as a Pashtoon Poet . Prior to the establishment of the Rampoor State , The Govt of Rohil Khand was being run as per tribal system . By the end of 18th century Dehli and Lucknow literary circles have developed an identity in urdu poetry, however, the Rampoor state was still infant as individually strong poets were anonymous. The chief factor behind this was the Political scenario of the state. Nawab's name emerged as venerable along with the poets of the era. He did not restrict himself to personal achievements but also led others in their professional skills. His ''Deewan" no more exists but we can get adequate range of his poetic work from Qudratullah's "Tazkira -e-Tabqatushuara".
Keywords: Evaluates; Establishment; State; Scenario; Tribal; Literary; Infant; Anonymous; Restrict; Skills; Emerged; Adequate